Zonal statistics datasets of climate indicators for Brazilian municipalities - Raphael Saldanha; Reza Akbarinia; Marcel Pedroso; Victor Ribeiro; Carlos Cardoso; Eduardo H. M. Pena; Patrick Valduriez; Fabio Porto (Environmental Data Science, 2024)
Climate trends and weather indicators are used in several research fields due to their importance in statistical modeling, frequently used as covariates. Usually, climate indicators are available as grid files with different spatial and time resolutions. The availability of a time series of climate indicators compatible with administrative boundaries is scattered in Brazil, not fully available for several years, and produced with diverse methodologies. In this paper, we propose time series of climate indicators for the Brazilian municipalities produced using zonal statistics derived from the ERA5-Land reanalysis indicators. As a result, we present datasets with zonal statistics of climate indicators with daily data, covering the period from 1950 to 2022.